2015
DOI: 10.1103/physreva.91.012708
|View full text |Cite
|
Sign up to set email alerts
|

Ultracold chemistry with alkali-metal–rare-earth molecules

Abstract: A first principles study of the dynamics of 6 Li( 2 S)+ 6 Li 174 Yb( 2 Σ + )→ 6 Li2( 1 Σ + )+ 174 Yb( 1 S) reaction is presented at cold and ultracold temperatures. The computations involve determination and analytic fitting of a three-dimensional potential energy surface for the Li2Yb system and quantum dynamics calculations of varying complexities, ranging from exact quantum dynamics within the close-coupling scheme, to statistical quantum treatment, and universal models. It is demonstrated that the two simp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 81 publications
(121 reference statements)
2
51
2
Order By: Relevance
“…The picture is further simplified because the anisotropy is not strong enough to reorient the reactants at long separations and an averaged, effective long-range potential emerges. Kotochigova and colleagues predicted that such averaging can give rise to an isotropic van der Waals interaction at long range in the universal limit, for ultracold Li + LiYb interactions, which are strongly anisotropic at short range 31 . In the case of He(2 3 P 2 ) + H 2 , the long-range interaction is characterized mainly by the van der Waals attraction, which scales as R -6 , and the quadrupole-quadrupole interaction, with a different scaling of R -5 .…”
Section: Resultsmentioning
confidence: 98%
“…The picture is further simplified because the anisotropy is not strong enough to reorient the reactants at long separations and an averaged, effective long-range potential emerges. Kotochigova and colleagues predicted that such averaging can give rise to an isotropic van der Waals interaction at long range in the universal limit, for ultracold Li + LiYb interactions, which are strongly anisotropic at short range 31 . In the case of He(2 3 P 2 ) + H 2 , the long-range interaction is characterized mainly by the van der Waals attraction, which scales as R -6 , and the quadrupole-quadrupole interaction, with a different scaling of R -5 .…”
Section: Resultsmentioning
confidence: 98%
“…In the ultracold regime, a single partial wave (i.e., the l=0 angular momentum partial wave or s-wave for bosons and distinguishable particles, and l=1 or p-wave for identical fermions) contributes to the scattering cross sections and the ultracold reaction rate coefficients obey the well known Bethe-Wigner threshold laws [74][75][76][77][78]. For exoergic processes these rate coefficients approach finite measurable values comparable to or even larger than their values at thermal energies [64][65][66][67][68][79][80][81][82][83]. The tiny kinetic energy associated with ultracold collisions makes them amenable to control via external electric or magnetic fields [69][70][71][72][84][85][86][87].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier, it has also been successfully applied to the Li + LiYb reaction. 218 González-Martínez et al 260 have recently implemented a statistical capture model for ultracold reactions in external fields and applied it to KRb + KRb → K 2 + Rb 2 and K + Rb 2 → Rb + KRb reactions. The performance of the capture model in the multiple-partial-wave regime (∼1 K) was recently assessed for the Li + CaH→ LiH + Ca chemical reaction and good agreement was found between the measured 96 and calculated values.…”
Section: Quantum Defect Theories and Capture/langevin Methodsmentioning
confidence: 99%
“…Ultracold chemistry involving alkali metal and alkaline earth metal atom systems has also been recently explored by Makrides et al 218 They investigated the Li + LiYb → Li 2 + Yb reaction at temperatures below 1 K using the hyperspherical coordinate approach in APH coordinates as well as statistical quantum (SQ) and MQDT approaches. It was found that the SQ and MQDT models yield comparable results as the full quantum calculations but the product quantum state distributions from the SQ method differed significantly from the full quantum results.…”
Section: E Field-free Reactive Scattering Calculationsmentioning
confidence: 99%